Revenue Equivalence Revisited - Radosveta Ivanova-Stenzel; Timothy C. Salmon (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
The conventional wisdom in the auction design literature is that first price sealed bid auctions tend to make more money while ascending auctions tend to be more efficient. We re-examine these issues in an environment in which bidders are allowed to endogenously choose in which auction format to participate. Our findings are that more bidders choose to enter the ascending auction than the first price sealed bid auction and this extra entry is enough to make up the revenue difference between the formats. Consequently, we find that both formats raise approximately the same amount of revenue. They also generate efficiency levels and bidder earnings that are roughly equivalent across mechanisms though the earnings in the ascending might be slightly higher. In expected utility terms though, we find that the expected utility of entering a first price sealed bid auction is greater than entering an ascending for any risk averse bidder suggesting that we are seeing 'overentry' into the ascending auctions.
urn:nbn:de:bvb:19-epub-13376-7
Keywords: C91; D44; 330; bidder preferences; private values; sealed bid auctions; ascending auctions; endogenous entry